Emergence of Quinolone Resistance in E. coli-associated Coliform Mastitis: A Case Report - Hima, K.M.; A.Janus; J.Alex; P.M.Deepa; R.L.Rathish; Biju P.Habeeb; F.A.Lali (The Indian Veterinary Journal, 2026)
A four-year-old Holstein Friesian crossbred cow with coliform mastitis showed poor response to enrofloxacin. Escherichia coli isolated from milk was multidrug resistant, with an enrofloxacin MIC >1024 µg/mL and QRDR mutations in gyrA (Ser83Leu and Asp87Asn) and parC (Ser80Ile). Gentamicin therapy resulted in complete recovery.